Green Training and Development Influencing Employee Green Behavior: The Mediating Role of Employee Green Attitude and Intentions in Lebanese Small and Medium-sized Enterprises - AlDana, Mona; Abbas , Alaa Elddine; Jneid, Cherine; Mosleh, Sara (International Review of Management and Marketing, 2026)
Environmental challenges have intensified interest in how green human resource management (GHRM) practices influence employee green behavior, yet prior studies frequently report non-significant relationships between aggregated GHRM practices and employee attitudes. Addressing this inconsistency, the present study disaggregates GHRM by examining green training and development as a focal practice and tests the mediating roles of employee attitude toward green behavior and green behavioral intention, drawing on the Ability–Motivation–Opportunity framework and the Theory of Planned Behavior. Data from a cross-sectional survey of 367 employees in Lebanese small and medium-sized enterprises were analyzed using partial least squares structural equation modeling. The results demonstrate that green training and development significantly influences employee attitudes toward green behavior, which in turn correlate with green behavioral intention and employee green behavior; green behavioral intention also directly predicts employee green behavior. Mediation analyses show that attitude and intention operate as distinct mechanisms linking green training and development to behavior. By disaggregating GHRM practices, this study successfully addresses and explains prior null findings and provides evidence that specific practices, rather than aggregated bundles, shape employee attitudes and behavior in SME and emerging-economy contexts.